2015
DOI: 10.3174/ajnr.a4585
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Subependymal Gray Matter Heterotopias on Fetal MRI

Abstract: BACKGROUND AND PURPOSE: Subependymal grey matter heterotopias are seen in a high proportion of children with Chiari II malformation and are potentially clinically relevant. However, despite its growing use, there is little in the literature describing its detection on fetal MRI. Our aim was to evaluate the accuracy in diagnosing subependymal gray matter heterotopias in fetuses with spinal dysraphism on fetal MR imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Postnatal evaluation would most likely have identified additional findings, such as subependymal heterotopias. 18,39 These are often missed in utero before as well as after fetal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Postnatal evaluation would most likely have identified additional findings, such as subependymal heterotopias. 18,39 These are often missed in utero before as well as after fetal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These cortical surface changes may be multifactorial and not wholly influenced by the Chiari II malformation alone. There have been several hypotheses put forward on the processes that underlie normal gyrification and fetal brain such as genetic control, or abnormal white matter development and neural tract damage due to mechanical stretching from hydrocephalus in association with MMC [8][9][10][11][12][13][14][15]35].…”
Section: Discussionmentioning
confidence: 99%
“…The constellation of brain changes comprising the Chiari II malformation (CIIM) which include small posterior fossa, caudal displacement of hindbrain structures and supratentorial anomalies [4,5] may be partly responsible either directly or by causing hydrocephalus through abnormal CSF circulation [6,7]. Hydrocephalus requires treatment with ventriculoperitoneal shunts in up to 80% of cases and causes mechanical stretching of brain parenchyma leading to abnormal unmyelinated white matter development which can be illustrated in diffusion tensor imaging (DTI) studies [8][9][10][11][12][13][14][15]. This neural tract damage can predispose to supratentorial anomalies such as altered gyrification patterns (e.g., polymicrogyria) and periventricular nodular heterotopia [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that this is related to ventricle size and intraventricular pressure affecting neuronal migration since in a previous study, we demonstrated a higher rate of fetal ventriculomegaly in patients with postnatally confirmed subependymal grey matter heterotopias. However, this was incompletely evaluated and requires further study …”
Section: Discussionmentioning
confidence: 99%